Reassessing legal humanism and its claims : petere fontes? - Plessis, Paul J. du; Cairns, John W. (Edinburgh : Edinburgh University Press, 2017)
This text is a fundamental reassessment of the nature and impact of legal humanism on the development of law in Europe. It brings together the foremost international experts in related fields such as legal and intellectual history to debate central issues surrounding this movement.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 1, 2016).
Keywords: Law, Medieval -- History; Humanism -- History -- To 1500.; Law; Jurisprudence & general issues